The Effect of Work Mutation and Position Promotion on Employee Work Performance Through Job Satisfaction as an Intervening Variable in The Service Padang City Trade - Sekhana, Raimul; Wijaya, Ronni Andri; Putra, Ramdani Bayu; Fitri, Hasmaynelis (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study aims to determine and analyze the effect of job mutations and promotion on job satisfaction of employees of the Padang City Trade Office. This research uses a quantitative type of research. The independent variables used are job mutations (X1) and promotion (X2), the dependent variable is job performance (Y), and the intervening variable is job satisfaction (Z). The sample selection technique used a clear sample, with a total of 94 employees of the Padang City Trade Department. The results of this study are job mutations that have a positive and significant effect on job satisfaction at the Padang City Trade Office. Job promotions have a positive and significant effect on job satisfaction at the Padang City Trade Department. Job transfers have a positive and significant effect on work performance at the Padang City Trade Service. Job promotions have a positive and significant effect on work performance at the Padang City Trade Service. Job satisfaction does not have a significant effect on work performance at the Padang City Trade Service. Job transfers do not have a significant effect on work performance through job satisfaction as an intervention at the Padang City Trade Service. Job promotion does not have a significant effect on work performance through job satisfaction as an intervention at the Padang City Trade Service.